Effect of antenna size on rock mass breaking efficiency under open-ended microwave treatment - Xue, Shou-Ning; Zhang, Yang; Luo, Jun; Xu, Fei-Long; Yang, Ben-Gao (Thermal science, 2025)
Antenna size is a critical factor influencing the efficiency of open-ended microwave rock-breaking. An electromagnetic-thermal-mechanical coupling model was developed to systematically investigate the influence of antenna size on the temperature distribution within the rock mass under microwave treatment. Furthermore, the evolution of rock mass damage was analyzed based on the stress filed induced by microwave treatment. The results demonstrate that decreasing the antenna size can significantly enhance the electromagnetic power loss density, thereby accelerating the rock-breaking process. However, a moderate increase in antenna size can broaden the extent of rock mass damage and improve the overall efficiency of microwave energy utilization.